ORGANIZAÇÃO E LUTA SINDICAL FACE AO NEOLIBERALISMO NO BRASIL: do novo sindicalismo à construção de alternativas à esquerda. - ALBUQUERQUE, Denise de Jesus (2019)
This dissertation analyzes the Brazilian trade union movement in the context of the implementation of the neoliberal project, having as main frame the governments of. ). In order to do so, we seek to understand the repercussions of the process of capitalist restructuring - anchored in productive restructuring, financialization and neoliberal ideology - evidenced in the late 1970s under the world of labor and the trade union movement. In the analysis of the particularity of Brazil, we bring a brief history of the Brazilian trade union movement, highlighting the new unionism that gave rise to the Central Única dos Trabalhadores (CUT) in the 1980s. We have verified that the victory of the neoliberal project in Brazil, with Collor's election in 1989, together with the collapse of the USSR and the crisis of the social-democratic syndicate model, put the main reference of Brazilian combative unionism, CUT, on the defensive, with its adherence to pro-union syndicalism. As part of the neoliberal strategy of contesting the leadership of the trade union movement, we also had the creation of the Força Sindical, in 1991, a center that is already born neoliberal, with its trade unionism. In this way, we analyze the performance of the two main trade union centers operating in the 1990s, pointing out their divergences and approximations in that decade, in view of the seasonal change of the era. With the election of Lula in 2002, there is a complete adhesion of the CUT to the project of conciliation of classes implemented by the Workers' Party. This being one of the elements responsible for the reorganization process of the Brazilian trade union movement, which began in the 2000s and is still under way, we also make some reflections on the construction of alternatives to the left of cutista trade unionism, with the creation of CSP-Conlutas. This center, with a trade union and popular character, has tried to fill the gap left by the Central Única dos Trabalhadores with regard to the organization of trade union struggles in Brazil, in the confrontation with 21st century neoliberalism.